USING NEW METHODS IN THE PRESCHOOL EDUCATION SYSTEM - Gulasal Tursunaliyeva (Bright Mind Publishing, 2025)
The development of the preschool education system involves creating new methods to solve the problems of increasing the physical activity of children from birth to preschool age and developing their physical qualities.
Keywords: Preschool children, raising a healthy child, physical education, development, mental preparation.